Qari (Male Voice) Increases Higher Expression of Synapsin 1 than Qariah (Female Voice) in the Cerebrum Newborn Rattus Norvegicus - Nur Laila Faizah; Hermanto Tri Joewono; Widjiati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Pregnancy is the golden period to prepare children for the future. Stimulation is neededduring pregnancy, one of which is brain stimulation. This can be done with Al Qur’an Murrotal SurahAr-Rahman stimulation. This study aims to analyze expression of synapsin 1 in the cerebrum of newbornRattus norvegicus when given murrotal Surah Ar-Rahman stimulation by qari, qariah, and not given anystimulation during pregnancy.Methods: Experimental with post-test only control group design. Sampling in this study was consideredhomogeneous because it met the inclusion criteria. The samples obtained were distributed randomly to eachexperimental group and randomized into 3 groups, including control group, group stimulated by qari, andgroup stimulated by qariah. The treatment was given on the 6th day of pregnancy for 1 hour in a soundproofroom with an intensity of 65 dB.Results: The highest mean expression of synapsin 1 in the cerebrum is qari group (6.96 ± 2.59), then qariahgroup (5.84 ± 2.90), and the lowest is control group (5.74 ± 2.32). There is no significant difference inexpression of synapsin 1 in the cerebrum between control and qari groups (p = 0.306), control and qariahgroups (p = 0.932), qari and qariah groups (p = 0.347).Conclusion: The highest expression of Synapsin 1 in the cerebrum of newborn Rattus norvegicus is thegroup stimulated by qari.